Epidemiology of rabies in Peru, 1984-2018 - Lopez Ingunza, Ricardo (2025)
The objective of this research was to describe the epidemiology of human and animal rabies in Peru from 1984 to 2018. The study population included the positive cases of rabies diagnosed in the laboratories of the INS, SENASA and the Centro Antirrábico de Lima, during the period indicated. A total of 10,354 rabies diagnoses were made, of which 97.3% (10,075) corresponded to animal rabies and 2.7% (279) to human rabies. These cases of human and canine rabies occurred in a similar way, in all the departments of Peru with the exception of Huancavelica and Ica, with dogs and bats being reservoirs. The most affected animals were: dogs 65% of cases, cattle 26.2%, cats 2.95%, bats 1.4% and the rest of the animals 4.4%. Canine rabies decreased during the 35 years of study, persisting in the departments of Arequipa and Puno, the opposite of bat rabies with an increasing trend in Apurímac, San Martín and Ayacucho. It is concluded that during the years from 1984 to 2018, rabies reservoirs (dog and bat) infected people and animals in almost all of the country's departments, with the exception of Huancavelica and Ica where there were no human deaths. The rabies epizootic was transmitted to other animals such as: cattle, cats, bats, etc. Although canine rabies has decreased in the study period, remaining endemic in the departments of Puno and Arequipa, bat rabies has increased in Apurímac, San Martín and Ayacucho.